Features of the borates in kimberlite rocks (Proceedings of Voronezh State University. Series: Geology, 2025)
Introduction: the conducted studies have shoun a wide variety of kimberlite diatremes on ancient platforms of the world in size, morphokogy and depln of the foci, the internal Structure, the features of the composition of billing rocks, the content and Composition of primary (deep) minerals, the composition of bulk of kimberlites the degaee and nature of the processing of the latter in postmagmatic and hypergepic conditions and features. Some of the listed features of kimberliteare due to the manitestation of endogenous factors and some are exogenous. Of particulat importance the presence around the kimberlite diatremes of the Siberian Platform (SP) of terrigenous-carbonate formations of the Silurian, Ordovician, Lower, Midale and Upper Cambrian, represented by limestones dolomites, mergelites and intermediate differenes of these rocks. In the central part the section of the host rocks. Especially high concentrations of the latter werw found in the Lower Cambrion Sediments of depths of 900-1200 m.Significant volumes, of highly minerakized waters (prines) were also buried in the Lower Cambrium sediments,which Significantly affected the material composition of kimberlites in diatremes discovered in this territory. The composition of the strata containing the diatremes, the geokogicak and structurak features, of their placement, the degrec of pneumalite-hydrothermal and hypergenie transformation leol to abunden secondary transformation of kimberlites, in many cases turhing them info apokimberlites.Оbjects, research methodology and discussion of the result: among secondary minerals of kimberlites of some Siberian platform (SP) diatremes borates have been identified, discovered in small saline veins and veinlets. Ekaterinite associates with colorless, orange-red and bluish halite, anhydrite, calcite and serpentine. Ekaterinite usually forms sinter inclusions in orange-red halite in bulges of small veins, and in veinlets it is observed in the form of aggregates, individuals in which are located along the long side in parallel to each other and perpendicularly to substrate. The color of ekaterinite changes from pink- to cherry-red, and orange-red segregations of the mineral dominate in monogene veinlets. Mixture of oxides and ferric hydroxides serves as the coloring matter. Some individuals of ferroszaibelyite have prolate shape. In some cases individuals resemble laths, in others – they are needle-shaped. Development of prolate segregations of ferroszaibelyite to some degree is conditioned by specificity of their growth and by structure of the mineral proper (chain structure of borates) as well. The mineral is usually of brown color. In kimberlite pipes boric minerals occur in small veins and veinlets of halite, crossing serpentinous kimberlite at individual depths. Since boric minerals are usually related with salts, there is a supposition that boron was brought into kimberlites together with soluble salts from hosting sedimentary saliferous deposits. In the course of serpentinization boron practically scatters and only at magnesia available, together with brucite, insignificant quantity of ascharite emerges. Direct dependence of boron content on composition of volatile phase is observed for kimberlites, under influence of which their metasomatic alteration is realized.Conclusion: that is why enrichment of underground brines by boron should be connected to a significant degree with abyssal sources of this element. Magnesium and iron (Fe), necessary for formation of ferroszaibelyite, were mobilized from pore solutions of hardening serpentine, which become nearly purely magnesia with lowering of temperature. Ekaterinite was formed in other than ferroszaibelyite conditions in oxide environment, about which inclusions in mineral of oxides and ferric hydroxides testify.
Keywords: kimberlites; ekaterinite; ferrossaibeliite; borate genesis